Immobilized lipase catalyzed production of methyl laurate from coconut oil. - Azucena, Vivian Amador (2000.)
Lipases from Carica papaya latex (CPL) and Rhizopus sp. II (RSII) were immobilized using silica gel support. Characterization of the immobilized Carica papaya latex lipase (IML-CPL) showed optimal ph and temperature values of 7 and 70 degrees centigrade repectively, while incubation time was optimum at 60 minutes. Kinetic studies showed that the IML-CPL has a Km of 0.20M and a Vmax of 4.12 Units/mg., A two-step process of enzymmatic methyl laurate production involving lipolysis of coconut oil and esterification of the free fatty acid was employed. Separation of the lipolytic product was done through urea complexion. The effect of different acyl donors on synthesis showed highest molar conversion of 73.90% with commercial lauric acid (Std-LA) as substrate, 39.33% with coconut oil (CNO-LA) and 11.46% with trilaurin. The use of shake-flask system showed higher product concentration than synthesis using the stirred-flask system. Optimization using the two immobilized lipases with lauric acid and coconut oil as substrate showed that highest product concentration was obtained at 55 degrees centigrade, while the optimal substrate/methanol ratio was at 0.505 mmmol/mmol. The reaction time needed by immobilized Carica papaya latex lipase was observed to be shorter than that required by Rhizopus sp. II lipase. Highest product concentration was obtained at 11.11 mmol added water with Rhizopus sp. II lipase. The immobilized Carica papaya latex lipase remained active after seven repeated use while the immobilized Rhizopus sp. II lipase exhibited inactivation after the fifth reuse. Gas chromatographic analysis was used to identify and quantify the products.
Thesis (Graduate, Master of Science (Biochemistry) Graduate School, University of the Philippines, Los Banos, Laguna. 2000.
Keywords: Coconut oil; Coconut Oil -- Methyl laurate